Epoxy resin composition, flame-retardant epoxy resin and preparation method and application thereof
By designing the epoxy resin composition and utilizing the conjugated rigid structure composed of Schiff base and benzene ring, the problem of unsatisfactory performance of existing epoxy resins in the application of hydrogen storage bottles has been solved, and low viscosity, high strength and excellent performance have been achieved. Flame retardant properties and high glass transition temperature, suitable for high-performance hydrogen storage bottles.
Patent Information
- Application Number
- CN202411873815.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-12-19
AI Technical Summary
The performance of existing epoxy resins in hydrogen storage cylinder applications does not meet the requirements, including high viscosity, flammability, and difficulty in achieving low curing temperatures and high glass transition temperatures.
By designing a type of epoxy resin composition, using the common rigid structure composed of Sptine and benzene ring to form a dense cross -linking structure, improve the strength and glassization of the resin, and prepare , Enhance flame retardant performance.
Epoxy resin, which has achieved low viscosity, high strength, excellent flame retardant performance, and high glass transformed temperature. It is suitable for type IV full -wound hydrogen storage cylinder, reducing the curing temperature and thermal release amount, and improving safety and fire prevention and control. ability.
Smart Images

Figure CN119331224A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of epoxy resins, and in particular to an epoxy resin composition, a flame-retardant epoxy resin, and a preparation method and application thereof. Background Art
[0002] Epoxy resin (EP) has the advantages of high bonding strength, small curing shrinkage, no small volatile molecules, good processability, heat resistance, good chemical stability, low cost, wide sources and reasonable price, and the adjustability of the molecular structure enables the applicability and functionality of the monomer to be adjusted. It is widely used in aerospace, machinery manufacturing, electronic engineering, transportation and other fields. However, the inherent disadvantages of cured epoxy resin systems, such as brittleness or lack of crack propagation resistance caused by high crosslinking density and strong covalent network, and the high risk of fire caused by the flammability of epoxy resin itself, have limited its development in many fields.
[0003] However, the development of high-performance epoxy resins faces two obstacles: (1) the unsustainability of its petroleum-based raw materials in the life cycle, from production, use to disposal; and (2) the difficulty in further improving special properties, such as dielectric properties and flame retardancy. At present, most epoxy resins are derived from petroleum resources, especially bisphenol A epoxy resins. Petroleum resources are a non-renewable resource. With the decreasing reserves, the cost of polymer materials derived from petroleum resources will inevitably increase. In addition, bisphenol A is suspected of physiological toxicity and has been restricted in many countries such as Europe. Therefore, in the current situation of increasingly depleted petroleum resources, it is urgent to use raw materials from other sources to produce epoxy resins and reduce dependence on petroleum resources. Finding sustainable, high-quality, cheap, and non-toxic petroleum substitutes is the key to the existence and development of the polymer industry. It is particularly important to develop substitutes with renewable resources and comparable performance.
[0004] The development trend of hydrogen storage bottle technology is lightweight, high pressure, high hydrogen storage density, and long life. Compared with traditional metal materials, polymer composite materials can reduce the wall thickness of the storage tank while maintaining the same pressure resistance level, increase the capacity and hydrogen storage efficiency, and reduce the energy consumption cost during long-distance transportation. Therefore, the performance of epoxy resin in the composite material is the key to the preparation of Type IV hydrogen storage cylinders, requiring the resin to have a low curing temperature, a short curing time, a high glass transition temperature, and good rigidity of the composite material.
[0005] The viscosity of epoxy resin is also one of the most important indicators of epoxy resin performance. Lower viscosity is conducive to the application of epoxy resin in the field of winding molding. However, DGEBA (bisphenol A epoxy resin) itself has high viscosity, which makes processing challenging. In response to this, researchers often add diluents to DGEBA to reduce viscosity and improve fluidity and processability. Although this method improves processing performance to a certain extent, the use of additives affects other properties, such as thermal stability, mechanical properties and glass transition temperature. Therefore, designing a low-viscosity, high-performance epoxy resin based on the molecular structure not only eliminates the step of adding fillers, but also does not reduce the performance of the resin itself, which is extremely popular in industrial production.
[0006] Chinese patent document CN118755051A "A low-viscosity high-equivalent epoxy resin and its preparation method and application" (published on October 11, 2024) discloses a method of reducing viscosity by partially modifying epoxy resin with amic acid, and proposes a solution to the problem that it is difficult to prepare low-viscosity high-equivalent epoxy resin without using active diluents. However, this resin itself is not flame retardant, and the raw materials have a large impact on the environment. The preparation process is complicated, the performance improvement is not obvious, and it is difficult to achieve large-scale production and application. Summary of the invention
[0007] In order to solve the problem that the performance of existing epoxy resins for hydrogen storage cylinders does not meet the production and application requirements, the present invention provides an epoxy resin composition, a flame retardant epoxy resin, and a preparation method and application thereof.
[0008] The technical solution of the present invention is as follows: An epoxy resin composition, wherein the structural formula of the epoxy resin composition is one of the following structural formulas: .
[0009] The present invention also provides a method for preparing the epoxy resin composition, comprising the following steps: S1. Dissolve 2-(4-hydroxyphenyl)ethylamine in a solvent under a nitrogen atmosphere, add hydroxybenzaldehyde, and reflux to react. Precipitate the crude product with deionized water, then purify with methanol and ethanol, evaporate the solvent in vacuo, and dry in vacuo to obtain the intermediate TSA. S2. Dissolve the intermediate in 3-chloropropylene oxide under a nitrogen atmosphere, then add tetrabutylammonium bromide and reflux for reaction. After cooling the solution to 50° C., add aqueous sodium hydroxide solution to continue the reaction. After the reaction is completed, cool the mixture to room temperature, wash repeatedly with deionized water to remove by-products, add an appropriate amount of anhydrous magnesium sulfate to dry the reaction mixture overnight, then evaporate, and then vacuum dry to remove unreacted 3-chloropropylene oxide to obtain the target product, flame retardant epoxy resin TSE.
[0010] Preferably, the hydroxybenzaldehyde is o-hydroxybenzaldehyde, m-hydroxybenzaldehyde or p-hydroxybenzaldehyde.
[0011] Preferably, the solvent of step S1 is anhydrous ethanol; the temperature of the reflux reaction is 70° C., and the time of the reflux reaction is 4 h to 6 h.
[0012] Preferably, the temperature of the reflux reaction in step S2 is 100° C., the time of the reflux reaction is 2 h to 4 h, the evaporation time is 1 h to 3 h, and the vacuum drying time is 12 h to 14 h.
[0013] Preferably, the mass concentration of the sodium hydroxide aqueous solution is 40wt%, and the reaction time after adding the sodium hydroxide solution is 4h~6h.
[0014] The present invention also provides a flame retardant epoxy resin, which is formed by curing the epoxy resin composition.
[0015] A method for preparing the flame retardant epoxy resin comprises the following steps: The epoxy resin composition is mixed with a curing agent, stirred evenly and placed in a vacuum oven. When the mixture has no bubbles in a vacuum, it is quickly poured into a mold preheated at 70° C., and then cured at 75° C. for 1 hour, and then the temperature is adjusted to 110° C. and cured for another 3 hours to obtain a flame-retardant epoxy resin.
[0016] Preferably, the curing agent is 4,4'-diaminodiphenylmethane.
[0017] The present invention also provides an application of the epoxy resin composition or the flame-retardant epoxy resin, specifically, it is used as a raw material for preparing the wall of a type IV fully wound hydrogen storage cylinder.
[0018] Compared with the prior art, the specific beneficial effects of the present invention are: The conjugated rigid structure composed of the Schiff base and the benzene ring in the epoxy resin composition provided by the present invention can form a denser cross-linked structure, thereby improving the resin strength, modulus, and glass transition temperature. At the same time, the Schiff base degrades into carbon earlier, which can hinder the further degradation of the polymer matrix and prevent combustion. The dense carbon layer forms an oxide protective film on the surface of the material, which can prevent the diffusion and propagation of the flame, reduce the combustion rate, inhibit the generation of combustible gas, flame retardant oxidation and thermal decomposition, thereby reducing the released heat. The reduction in the amount of heat release is conducive to the overall combustion environment being suitable for personnel to escape, and can also reduce the ignition of nearby non-flame retardant materials.
[0019] The new low-viscosity enhanced intrinsic flame-retardant epoxy resin provided by the present invention is prepared using green renewable bio-based raw materials, is environmentally friendly, and has low viscosity, high strength, high glass transition temperature, excellent flame retardant properties, and reduces the curing temperature. It not only provides a new choice for the field of high-performance epoxy resins, but also provides a more suitable resin matrix for hydrogen energy, especially type IV fully wound hydrogen storage cylinders. Small molecule flame-retardant epoxy resin TSE can effectively reduce the viscosity of the mixture to achieve a suitable viscosity for wet winding of type IV hydrogen storage cylinders, better infiltrate carbon fibers and reduce the generation of bubbles; the lower curing temperature can ensure that the plastic liner of the type IV hydrogen storage cylinder will not fail due to high temperature after the composite material is cured, and the overall loading pressure of the cylinder is not affected by the collapse of the liner; the higher glass transition temperature can increase the working temperature of the hydrogen storage cylinder while improving safety.
[0020] The reaction process of the invention is easy to operate, the preparation method is simple, and it is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is the infrared spectrum of the reactants and products at each stage in Example 1; Figure 2 The viscosity of the flame retardant epoxy resin TSE prepared in Example 1 and the bisphenol A epoxy resin in the comparative example varies with temperature; Figure 3 The rheological diagrams of the flame retardant epoxy resin TSE prepared in Example 1 and the bisphenol A epoxy resin in the comparative example; Figure 4 The figure is a bar graph showing the flexural strength and flexural modulus of the flame retardant epoxy resin TSE prepared in Example 1 and the bisphenol A epoxy resin in the comparative example; Figure 5 1 is the stress-strain curve of the flame-retardant epoxy resin TSE prepared in Example 1 and the bisphenol A epoxy resin in the comparative example; Figure 6 It is a bar graph of the impact strength of the flame retardant epoxy resin TSE prepared in Example 1 and the bisphenol A epoxy resin in the comparative example; Figure 7 It is a comparison chart of the heat release rate of the flame retardant epoxy resin TSE prepared in Example 1 and the bisphenol A epoxy resin in the comparative example; Figure 8 It is a comparison chart of the total heat release of the flame retardant epoxy resin TSE prepared in Example 1 and the bisphenol A epoxy resin in the comparative example; Fig. 9 This is a comparison chart of carbon monoxide release rates of the flame retardant epoxy resin TSE prepared in Example 1 and the bisphenol A epoxy resin in the comparative example; Fig.10 This is a comparison chart of smoke generation rates of the flame retardant epoxy resin TSE prepared in Example 1 and the bisphenol A epoxy resin in the comparative example; Fig.11 This is a comparison chart of the total smoke production of the flame retardant epoxy resin TSE prepared in Example 1 and the bisphenol A epoxy resin in the comparative example; Fig.12 This is a comparison chart of carbon dioxide release rates of the flame retardant epoxy resin TSE prepared in Example 1 and the bisphenol A epoxy resin in the comparative example; Fig.13 This is a comparison chart of the mass loss rates of the flame retardant epoxy resin TSE prepared in Example 1 and the bisphenol A epoxy resin in the comparative example; Fig.14 The limiting oxygen index bar graph of the flame retardant epoxy resin TSE prepared in Example 1 and the bisphenol A epoxy resin in the comparative example; Fig.15 This is a photo of the carbon residue from the cone calorimetry test of Example 1. DETAILED DESCRIPTION
[0022] In order to make the technical solution of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the specification of the present invention. It should be noted that the following embodiments are only used to better understand the technical solution of the present invention and should not be understood as a limitation to the present invention.
[0023] The raw materials and equipment used in the present invention are all known products, which are obtained by purchasing commercially available products.
[0024] Example 1. In a three-necked round-bottom flask, 2-(4-hydroxyphenyl)ethylamine (10 g, 0.07 mol) was dissolved in anhydrous ethanol under a nitrogen atmosphere. Subsequently, o-hydroxybenzaldehyde (8.6 g, 0.07 mol) was added to the above solution and refluxed at 70 °C for 5 h. The crude product was precipitated by deionized water and then purified with methanol and ethanol. After evaporating the solvent in vacuo, it was dried in vacuo at 70 °C for 12 h to obtain the desired intermediate TSA.
[0025] The reaction route is as follows: .
[0026] In a three-necked round-bottom flask, TSA (10 g, 0.041 mol) was dissolved in 3-chloropropylene oxide (76 g, 0.082 mol) under nitrogen atmosphere. TBAB (0.86 g, 0.0026 mol) was then added to the above solution and refluxed at 100 °C for 3 h. The above solution was cooled to 50 °C and 40 wt% sodium hydroxide aqueous solution (8.2 g, 0.082 mol) was added and the reaction was continued for 5 h. The mixture was then cooled to room temperature and the resulting solution was washed 7 times with deionized water to remove by-products. The reaction mixture was dried overnight by adding an appropriate amount of anhydrous magnesium sulfate. The dried reaction mixture was evaporated at 80 °C for 2 h and then placed in a vacuum oven at 80 °C for 12 h to completely remove unreacted 3-chloropropylene oxide. The target product TSE was obtained in a reddish brown color.
[0027] The reaction route is as follows: .
[0028] 1 part of molten diaminodiphenylmethane (DDM) was used as a curing agent, and 4 parts of TSE were added and mixed evenly. After stirring evenly, the mixture was placed in a vacuum oven. When there were no bubbles in the mixture in the vacuum, the mixed sample was quickly poured into the mold, the mold was preheated at 70°C for 20 minutes, and after curing at 75°C for 1 hour, the temperature was adjusted to 110°C and cured for 3 hours to obtain a flame-retardant epoxy resin.
[0029] The infrared spectra of the reactants and products at each stage in this example are as follows: Figure 1 As shown. It can be seen that 3334cm in the 2-(4-hydroxyphenyl)ethylamine curve -1 The disappearance of the -NH2 peak at 1668cm in the o-hydroxybenzaldehyde curve -1 The disappearance of the -CHO peak at 1634 cm -1 The appearance of the Schiff base (-C=N-) bond signal peak at 1470 nm indicates that TSA is successfully synthesized according to the above reaction route. In the flame-retardant epoxy resin TSE, -NH2 (3334 cm -1 ) peak and -CHO (1668cm -1 ) peak did not appear, and -C=N- (1634cm -1 ) The key signal peak is still maintained, and at the same time, the 914cm -1 The appearance of a new epoxy group signal peak confirmed the successful synthesis of TSE.
[0030] Example 2. In a three-necked round-bottom flask, 2-(4-hydroxyphenyl)ethylamine (12 g, 0.084 mol) was dissolved in anhydrous ethanol under a nitrogen atmosphere. Subsequently, o-hydroxybenzaldehyde (10.32 g, 0.084 mol) was added to the above solution and refluxed at 70 °C for 5 h. The crude product was precipitated by deionized water and then purified with methanol and ethanol. After evaporating the solvent in vacuo, it was dried in vacuo at 70 °C for 12 h to obtain the desired intermediate TSA.
[0031] In a three-necked round-bottom flask, TSA (12 g, 0.0492 mol) was dissolved in 3-chloropropylene oxide (91.2 g, 0.0984 mol) under nitrogen atmosphere. TBAB (1.032 g, 0.00312 mol) was then added to the above solution and refluxed at 100 °C for 3 h. After the above solution was cooled to 50 °C, 40 wt% sodium hydroxide aqueous solution (9.84 g, 0.0984 mol) was added and the reaction was continued for 5 h. The mixture was then cooled to room temperature and the resulting solution was washed 7 times with deionized water to remove by-products. The reaction mixture was dried overnight by adding an appropriate amount of anhydrous magnesium sulfate. The dried reaction mixture was evaporated at 80 °C for 1-3 h and then placed in a vacuum oven at 80 °C for 12 h to completely remove unreacted 3-chloropropylene oxide. The target product TSE was obtained in a reddish brown color.
[0032] Add 1 part of molten diaminodiphenylmethane (DDM) as a curing agent to 4 parts of TSE and mix well. Stir well and place in a vacuum oven. When there are no bubbles in the mixture in the vacuum, quickly pour the mixed sample into the mold, preheat the mold at 70°C for 20 minutes, and after curing at 70°C for 2 hours, adjust the temperature to 100°C and cure for 2 hours; adjust the temperature to 140°C and cure for 2 hours.
[0033] Example 3. In a three-necked round-bottom flask, 2-(4-hydroxyphenyl)ethylamine (20 g, 0.14 mol) was dissolved in anhydrous ethanol under a nitrogen atmosphere. Subsequently, o-hydroxybenzaldehyde (17.2 g, 0.14 mol) was added to the above solution and refluxed at 70 °C for 5 h. The crude product was precipitated by deionized water and then purified with methanol and ethanol. After evaporating the solvent in vacuo, it was dried in vacuo at 70 °C for 12 h to obtain the desired intermediate TSA.
[0034] In a three-necked round-bottom flask, TSA (20 g, 0.082 mol) was dissolved in 3-chloropropylene oxide (152 g, 0.164 mol) under nitrogen atmosphere. TBAB (1.72 g, 0.0052 mol) was then added to the above solution and refluxed at 100 °C for 3 h. The above solution was cooled to 50 °C and 40 wt% sodium hydroxide aqueous solution (16.4 g, 0.164 mol) was added and the reaction was continued for 5 h. The mixture was then cooled to room temperature and the resulting solution was washed 7 times with deionized water to remove by-products. The reaction mixture was dried overnight by adding an appropriate amount of anhydrous magnesium sulfate. The dried reaction mixture was evaporated at 80 °C for 2 h and then placed in a vacuum oven at 80 °C for 12 h to completely remove unreacted 3-chloropropylene oxide. The target product TSE was obtained in a reddish brown color.
[0035] Add 1 part of molten diaminodiphenylmethane (DDM) as a curing agent to 4 parts of TSE and mix well. Stir well and place in a vacuum oven. When there are no bubbles in the mixture in the vacuum, quickly pour the mixed sample into the mold, preheat the mold at 70°C for 20 minutes, cure at 80°C for 2 hours, adjust the temperature to 110°C, cure for 2 hours; adjust the temperature to 150°C, and cure for 2 hours.
[0036] Example 4. In a three-necked round-bottom flask, 2-(4-hydroxyphenyl)ethylamine (30 g, 0.21 mol) was dissolved in anhydrous ethanol under a nitrogen atmosphere. Subsequently, o-hydroxybenzaldehyde (25.8 g, 0.21 mol) was added to the above solution and refluxed at 70 °C for 5 h. The crude product was precipitated by deionized water and then purified with methanol and ethanol. After evaporating the solvent in vacuo, it was dried in vacuo at 70 °C for 12 h to obtain the desired intermediate TSA.
[0037] In a three-necked round-bottom flask, TSA (30 g, 0.123 mol) was dissolved in 3-chloropropylene oxide (228 g, 0.246 mol) under nitrogen atmosphere. TBAB (2.58 g, 0.0078 mol) was then added to the above solution and refluxed at 100 °C for 3 h. The above solution was cooled to 50 °C and 40 wt% sodium hydroxide aqueous solution (24.6 g, 0.246 mol) was added and the reaction was continued for 5 h. The mixture was then cooled to room temperature and the resulting solution was washed 7 times with deionized water to remove by-products. The reaction mixture was dried overnight by adding an appropriate amount of anhydrous magnesium sulfate. The dried reaction mixture was evaporated at 80 °C for 2 h and then placed in a vacuum oven at 80 °C for 12 h to completely remove unreacted 3-chloropropylene oxide. The target product TSE was obtained in a reddish brown color.
[0038] Add 1 part of molten diaminodiphenylmethane (DDM) as a curing agent to 4 parts of TSE and mix well. Stir well and place in a vacuum oven. When there are no bubbles in the mixture in the vacuum, quickly pour the mixed sample into the mold, preheat the mold at 70°C for 20 minutes, cure at 90°C for 2 hours, adjust the temperature to 120°C, cure for 2 hours; adjust the temperature to 160°C, and cure for 2 hours.
[0039] Example 5. In a three-necked round-bottom flask, 2-(4-hydroxyphenyl)ethylamine (40 g, 0.28 mol) was dissolved in anhydrous ethanol under a nitrogen atmosphere. Subsequently, o-hydroxybenzaldehyde (34.4 g, 0.28 mol) was added to the above solution and refluxed at 70 °C for 4-6 h. The crude product was precipitated by deionized water and then purified with methanol and ethanol. After evaporating the solvent in vacuo, it was dried in vacuo at 70 °C for 12 h to obtain the desired intermediate TSA.
[0040] In a three-necked round-bottom flask, TSA (40 g, 0.164 mol) was dissolved in 3-chloropropylene oxide (304 g, 0.328 mol) under nitrogen atmosphere. TBAB (3.44 g, 0.104 mol) was then added to the above solution and refluxed at 100 °C for 3 h. The above solution was cooled to 50 °C and 40 wt% sodium hydroxide aqueous solution (32.8 g, 0.328 mol) was added and the reaction was continued for 5 h. The mixture was then cooled to room temperature and the resulting solution was washed 7 times with deionized water to remove by-products. The reaction mixture was dried overnight by adding an appropriate amount of anhydrous magnesium sulfate. The dried reaction mixture was evaporated at 80 °C for 2 h and then placed in a vacuum oven at 80 °C for 12 h to completely remove unreacted 3-chloropropylene oxide. The target product TSE was obtained in a reddish brown color.
[0041] Add 1 part of molten diaminodiphenylmethane (DDM) as a curing agent to 4 parts of TSE and mix well. Stir well and place in a vacuum oven. When there are no bubbles in the mixture in the vacuum, quickly pour the mixed sample into the mold, preheat the mold at 70°C for 20 minutes, cure at 60°C for 1 hour, adjust the temperature to 100°C, and cure for 3 hours.
[0042] Example 6. In a three-necked round-bottom flask, 2-(4-hydroxyphenyl)ethylamine (10 g, 0.07 mol) was dissolved in anhydrous ethanol under nitrogen atmosphere. Subsequently, m-hydroxybenzaldehyde (8.6 g, 0.07 mol) was added to the above solution and refluxed at 70 °C for 5 h. The crude product was precipitated by deionized water and then purified with methanol and ethanol. After evaporating the solvent in vacuo, it was dried in vacuo at 70 °C for 12 h to obtain the desired intermediate TH3Y.
[0043] The reaction route is as follows:
[0044] In a three-necked round-bottom flask, TH3Y (10 g, 0.041 mol) was dissolved in 3-chloropropylene oxide (76 g, 0.082 mol) under nitrogen atmosphere. TBAB (0.86 g, 0.0026 mol) was then added to the above solution and refluxed at 100 °C for 3 h. The above solution was cooled to 50 °C and 40 wt% sodium hydroxide aqueous solution (8.2 g, 0.082 mol) was added and the reaction was continued for 5 h. The mixture was then cooled to room temperature and the resulting solution was washed 7 times with deionized water to remove by-products. The reaction mixture was dried overnight by adding an appropriate amount of anhydrous magnesium sulfate. The dried reaction mixture was evaporated at 80 °C for 2 h and then placed in a vacuum oven at 80 °C for 12 h to completely remove unreacted 3-chloropropylene oxide. The target product TH3E was obtained in a reddish brown color.
[0045] The reaction route is as follows:
[0046] 1 part of molten diaminodiphenylmethane (DDM) was used as a curing agent, and 4 parts of TH3E were added and mixed evenly. After stirring evenly, the mixture was placed in a vacuum oven. When there were no bubbles in the mixture in the vacuum, the mixed sample was quickly poured into the mold, the mold was preheated at 70°C for 20 minutes, and after curing at 75°C for 1 hour, the temperature was adjusted to 110°C and cured for 3 hours to obtain a flame-retardant epoxy resin.
[0047] Example 7. In a three-necked round-bottom flask, 2-(4-hydroxyphenyl)ethylamine (10 g, 0.07 mol) was dissolved in anhydrous ethanol under a nitrogen atmosphere. Subsequently, p-hydroxybenzaldehyde (8.6 g, 0.07 mol) was added to the above solution and refluxed at 70 °C for 5 h. The crude product was precipitated by deionized water and then purified with methanol and ethanol. After evaporating the solvent in vacuo, it was dried in vacuo at 70 °C for 12 h to obtain the desired intermediate TH4Y.
[0048] The reaction route is as follows:
[0049] In a three-necked round-bottom flask, TH4Y (10 g, 0.041 mol) was dissolved in 3-chloropropylene oxide (76 g, 0.082 mol) under nitrogen atmosphere. TBAB (0.86 g, 0.0026 mol) was then added to the above solution and refluxed at 100 °C for 3 h. The above solution was cooled to 50 °C and 40 wt% aqueous sodium hydroxide solution (8.2 g, 0.082 mol) was added and the reaction was continued for 5 h. The mixture was then cooled to room temperature and the resulting solution was washed 7 times with deionized water to remove by-products. The reaction mixture was dried overnight by adding an appropriate amount of anhydrous magnesium sulfate. The dried reaction mixture was evaporated at 80 °C for 2 h and then placed in a vacuum oven at 80 °C for 12 h to completely remove unreacted 3-chloropropylene oxide. The target product TH4E was obtained in a reddish brown color.
[0050] The reaction route is as follows:
[0051] 1 part of molten diaminodiphenylmethane (DDM) was used as a curing agent, and 4 parts of TH4E were added and mixed evenly. After stirring evenly, the mixture was placed in a vacuum oven. When there were no bubbles in the mixture in the vacuum, the mixed sample was quickly poured into the mold, the mold was preheated at 70°C for 20 minutes, and after curing at 75°C for 1 hour, the temperature was adjusted to 110°C and cured for 3 hours to obtain a flame-retardant epoxy resin.
[0052] Comparison ratio. 1 part of molten diaminodiphenylmethane (DDM) as a curing agent was added to 4 parts of bisphenol A epoxy resin (E51) and mixed evenly. After stirring evenly, it was placed in a vacuum oven. When there were no bubbles in the mixture in the vacuum, the mixed sample was quickly poured into the mold, the mold was preheated at 70°C for 20 minutes, and after curing at 120°C for 2 hours, the temperature was adjusted to 150°C and cured for 2 hours.
[0053] Effect example. The viscosity of the flame retardant epoxy resin TSE prepared in Example 1 and the bisphenol A epoxy resin in the comparative example varies with temperature. Figure 2 As shown in the rheological spectrum at 25°C Figure 3 As shown. It can be clearly seen that the viscosity of TSE is much lower than that of bisphenol A epoxy resin, which is only 0.539 Pa·s, much lower than the viscosity of bisphenol A epoxy resin 15.107 Pa·s. It can be proved that the fluidity and processability of the epoxy resin synthesized in this embodiment are greatly improved, and it is more suitable for industrial applications.
[0054] The flexural strength and flexural modulus bar graphs and stress-strain curves of the flame-retardant epoxy resin TSE prepared in Example 1 and the bisphenol A epoxy resin in the comparative example are shown in FIG. Figure 4 , Figure 5As shown in the figure, it can be seen that the flexural strength of TSE is 205Mpa, which is about 90% higher than the 108Mpa of bisphenol A epoxy resin, and the flexural modulus is also significantly improved; the tensile strength and elongation at break of TSE are almost twice that of bisphenol A epoxy resin.
[0055] The impact strength bar graph of the flame retardant epoxy resin TSE prepared in Example 1 and the bisphenol A epoxy resin in the comparative example is as follows: Figure 6 As shown. The impact strength of flame retardant epoxy resin TSE is 15.934KJ / m 2 Compared with 3.617KJ / m of bisphenol A epoxy resin 2 The improvement is 340%. The higher impact strength can ensure that the Type IV hydrogen storage cylinder can withstand greater external destructive force, ensuring the safety of personnel working in the Type IV hydrogen storage cylinder.
[0056] The cone calorimetry data of the flame retardant epoxy resin TSE prepared in Example 1 and the bisphenol A epoxy resin in the comparative example are as follows: Figures 7 to 14 shown. Fig.15 This is a photo of the burning carbon residue in the cone calorimetric test of Example 1. By comparison, it can be seen that the mass loss rate (MASS), smoke generation rate (SPR), heat release rate (HRR), and total heat release (THR) of the flame retardant epoxy resin TSE are significantly reduced compared with bisphenol A epoxy resin, and the TSE limiting oxygen index is as high as 35.5%. The above data can strongly prove that the use of TSE as a matrix resin can maximize the fire safety of type IV hydrogen storage cylinders during use.
[0057] The test results of the bending strength, bending modulus, impact strength, tensile modulus, tensile strength and other properties of the epoxy resins prepared in Examples 1 to 7 and the comparative example are shown in Table 1. By comparison, it can be seen that the flame retardant properties and various mechanical properties of the epoxy resin prepared by the present invention are significantly improved compared with the ordinary E51 epoxy resin on the market. When applied to type IV hydrogen storage cylinders, its performance, service life and personal safety of related personnel can be guaranteed to a greater extent.
[0058] Table 1
[0059] It is to be understood that the present invention is described by some embodiments, and it is known to those skilled in the art that various changes or equivalent substitutions may be made to these features and embodiments without departing from the spirit and scope of the present invention. In addition, under the teachings of the present invention, these features and embodiments may be modified to adapt to specific circumstances and materials without departing from the spirit and scope of the present invention. Therefore, the present invention is not limited by the specific embodiments disclosed herein, and all embodiments falling within the scope of the claims of this application are within the scope of protection of the present invention.
Claims
1. An epoxy resin composition, characterized in that The structural formula of the epoxy resin composition is one of the following structural formulas: 。 2. A method for preparing the epoxy resin composition according to claim 1, characterized in that: The steps include: S1. Dissolve 2-(4-hydroxyphenyl)ethylamine in a solvent under a nitrogen atmosphere, add hydroxybenzaldehyde, and reflux to react. Precipitate a crude product with deionized water, purify with methanol and ethanol, evaporate the solvent in vacuo, and then dry in vacuo to obtain an intermediate. S2. Dissolve the intermediate in 3-chloropropylene oxide under a nitrogen atmosphere, then add tetrabutylammonium bromide and reflux for reaction, cool the solution to 50°C and add aqueous sodium hydroxide solution to continue the reaction, after the reaction is completed, cool the mixture to room temperature, wash repeatedly with deionized water to remove by-products, add anhydrous magnesium sulfate to dry the reaction mixture overnight, then evaporate, and then vacuum dry to remove unreacted 3-chloropropylene oxide to obtain the target product epoxy resin composition.
3. The method for preparing the epoxy resin composition according to claim 2, characterized in that: The hydroxybenzaldehyde is o-hydroxybenzaldehyde, m-hydroxybenzaldehyde or p-hydroxybenzaldehyde.
4. The method for preparing the epoxy resin composition according to claim 2, characterized in that: In step S1, the solvent is anhydrous ethanol; the temperature of the reflux reaction is 70° C., and the time of the reflux reaction is 4 h to 6 h.
5. The method for preparing the epoxy resin composition according to claim 2, characterized in that: The temperature of the reflux reaction in step S2 is 100° C., the time of the reflux reaction is 2 h to 4 h, the evaporation time is 1 h to 3 h, and the vacuum drying time is 12 h to 14 h.
6. The method for preparing the epoxy resin composition according to claim 2, characterized in that: The mass concentration of the sodium hydroxide aqueous solution in step S2 is 40wt%, and the reaction time after adding the sodium hydroxide solution is 4h~6h.
7. A flame retardant epoxy resin, characterized in that: The epoxy resin composition according to claim 1 is cured.
8. A method for preparing a flame retardant epoxy resin as claimed in claim 7, characterized in that: The steps include: The epoxy resin composition is mixed with a curing agent, stirred evenly and placed in a vacuum oven. When the mixture has no bubbles in a vacuum, it is quickly poured into a mold preheated at 70° C., and then cured at 75° C. for 1 hour, and then the temperature is adjusted to 110° C. and cured for another 3 hours to obtain a flame-retardant epoxy resin.
9. The method for preparing a flame retardant epoxy resin according to claim 8, characterized in that: The curing agent is 4,4'-diaminodiphenylmethane.
10. Use of the epoxy resin composition according to claim 1 or the flame-retardant epoxy resin according to claim 7, characterized in that: Used for the preparation of Type IV fully wrapped hydrogen storage cylinder walls.
Citation Information
Patent Citations
Low-viscosity high-equivalent epoxy resin as well as preparation method and application thereof
CN118755051A
Epoxy resin material for wet winding and preparation method thereof
CN116162327A
Preparation of biomass epoxy resin with degradable and flame-retardant characteristics
CN116478065A